Water quality study at Tasik Chini in 2013 and 2016 during wet and dry season - Munirah, Che Nordin (2017)
The purpose of this study is to analyse water quality at Tasik Chini in 2013 and 2016. This study was conducted at five sampling stations which are at Sg. Gumum, Sg. Jerangking, Sg. Kenawar, Sg. Melai and Sg. Chini. A total of thirteen water quality parameters and twelve heavy metals were measured and Malaysian Department of Environment Water Quality Index (DOE-WQI) was calculated and classified according to the Interim National Water Quality Standard, Malaysia (INWQS). The physical and chemical variable such as pH, Electrical Conductivity (EC), Turbidity, Temperature, Total Suspended Solids (TSS), Suspended Solid (SS), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Ammoniacal Nitrogen (NH3-N), Nitrate (N), Potassium (K), Phosphorus (P) was analysis in-situ and laboratory experiments. Twelve parameters to identify heavy metals concentration are Iron (III) Oxide (Fe203), Silicon Dioxide (SiO2), Alaminium Oxide (Al203), Manganese Oxide (MnO), Potassium Oxide (K20), Titanium Dioxide (TiO2), Phosphorus pentoxide (p205), Barium Oxide (BaO) Lead Oxide (Pbo), Calcium Oxide (Cao), Sulphur Trioxide(SO3), and Zinc Oxide (ZnO) also had test by run ICP-MS. Result show that base on Malaysian WQI, the water in Tasik Chini is classified as class II, which suitable for recreational activities and body contact. According to the National Water Quality Standard for Malaysia, electrical conductivity (EC), Nitrate (NO-3) and ammoniacal nitrogen (NH3-N), Class I, While temperature, and turbidity into Class II. For biochemical oxygen demand (BOD), chemical oxygen demand (COD), dissolved oxygen (DO), pH, and Total Suspended Solids (TSS) classified into Class III. However, based on result, illegal logging, iron mining, industrial and agriculture activities have taken place in surrounding of the lake consequently affected the pollution of water at Tasik Chini.